Drag-and-Pop and Drag-and-Pick: Techniques for Accessing Remote Screen Content on Touch- and Pen-Operated Systems - Baudisch, Patrick; Cutrell, Ed; Robbins, Daniel; Czerwinski, Mary; Tandler, Peter; Bederson, Benjamin; Zierlinger, Alex (Human-Computer Interaction–INTERACT '03, 2003)
Drag-and-pop and drag-and-pick are interaction techniques designed for users of pen- and touch-operated display systems. They provide users with access to screen content that would otherwise be impossible or hard to reach, e.g., because it is located behind a bezel or far away from the user. Drag-and-pop is an extension of traditional drag-and-drop. As the user starts dragging an icon towards some target icon, drag-and-pop responds by temporarily moving potential target icons towards the user’s current cursor location, thereby allowing the user to interact with these icons using comparably small hand movements. Drag-and-Pick extends the drag-and-pop interaction style such that it allows activating icons, e.g., to open folders or launch applications. In this paper, we report the results of a user study comparing drag-and-pop with traditional drag-and-drop on a 15’ (4.50m) wide interactive display wall. Participants where able to file icons up to 3.7 times faster when using the drag-and-pop interface.